Management of OPC and Carbamate Poisoning in Intensive Care Unit of Enam Medical College & Hospital, Savar, Dhaka - Khanum, Easnem; Islam, Md Ashraful; Salim, Mohammad; Islam, SM Rafiqul; PK, Md Rezaul Haque (Journal of Enam Medical College, 2018)
Background: Bangladesh is an agriculture-dependent country. Organophosphorus insecticides are widely used for the better outcome of cultivation. It is used for suicidal purpose due to its easy availability all over the country. Worldwide, acute pesticide poisoning is causing major health problems with high mortality in developing countries. Objective: The objective of our study was to establish that early management of acute poisoning with organophosphorus and carbamate in ICU along with ventilatory support in severe respiratory distress reduces the mortality rate. Materials and Methods: This study was conducted in the Department of Anesthesiology & ICU in Enam Medical College & Hospital, Savar, Dhaka from January 2013 to December 2015. Total 84 patients with acute poisoning cases were selected. The diagnosis was confirmed by the history of ingestion of insecticides, observing clinical signs and symptoms and presence of foul smelling of poisonous agent. Management included supportive care, intubation, artificial ventilation in selective cases, administration of antidotes as loading and maintenance dose for atropinization with atropine and pralidoxime, antibiotics, anti-ulcerant, anticonvulsant, inotropic support (in severe hypotension) along with other symptomatic treatment. After stabilization, decontamination was started with removal of contaminated clothes, thorough wash with soap and water, irrigation of eyes with water and normal saline. Gastric lavage was given within 2 to 3 hours of ingestion of poison. Results: Acute poisoning was observed more in male (60.71%) than in female (39.29%) and in age group of 21–40 years (60.71%). Suicidal attempt was present in 97.61% cases and causes of suicidal poisoning were familial disharmony (76.19%), financial loss (14.28%) and failure in examination (9.52%). Organophosphate group poison ingestion was in 77.38% cases and carbamate group poison in 21.43% and both agents in 1.19% cases. Ventilatory support was given in 48.80% cases and 78.05% patients were successfully extubated from mechanical ventilator. Mean duration of ventilatory support was 2–14 days. Out of 84 patients, 75 (89.28%) survived and 9 (10.72%) patients expired. Fifty two (61.91%) patients were discharged within 4–6 days, 16 (19.04%) within 2–3 days, and 7 (8.33%) patients were discharged within 7–14 days. Conclusion: Early ICU admission and appropriate management of patients after ingestion of poisonous agent results in reduced morbidity and mortality. J Enam Med Col 2018; 8(3): 144-152